2019
DOI: 10.4103/jos.jos_104_18
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of malocclusion and orthodontic treatment need of school children in Northern Saudi Arabia

Abstract: OBJECTIVE: To evaluate the incidence of malocclusion and requirement for orthodontic treatment in the Saudi region of Hail city. MATERIALS AND METHODS: 520 Saudi participants between 7 and 12 years from Hail city were used in the research, all of whom were selected using a simple randomization method. For every participant, various malocclusion variables such as molar, canine, and incisor relationship, overjet, overbite, open bite, cross bite, scissor cross bite, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 18 publications
4
5
2
Order By: Relevance
“…In our study, with regards to IOTN-DHC, about 30.9% of children have been found to require definite orthodontic treatment need which was higher than that reported in previous studies conducted in Saudi Arabia (19,20). Another study by Alharbi (12) had reported a higher definite orthodontic treatment need compared to that seen in the present study.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In our study, with regards to IOTN-DHC, about 30.9% of children have been found to require definite orthodontic treatment need which was higher than that reported in previous studies conducted in Saudi Arabia (19,20). Another study by Alharbi (12) had reported a higher definite orthodontic treatment need compared to that seen in the present study.…”
Section: Discussioncontrasting
confidence: 68%
“…However, studies found that it has limitations, as it lacks sensitivity, related to choosing cases specific for preventive or interceptive orthodontics (17). IOTN was used in the present study as the validity and reliability of this index has been verified in previous studies (18)(19)(20).…”
Section: Discussionmentioning
confidence: 91%
“…In terms of Class II malocclusion, a prevalence of 9.5% was found in the present study. This result is almost similar to the findings of Narayanan et al,20 (9.3%) in contrast higher rate of Class II in that reported by Brito et al, 14 (19.2%), Almeida et al, 21 (38%), Bourzgui et al, 31 (24%), Reddy et al, 22 (13.9%), Sultan 25 , (21.93%), and by Alajlan et al,32 (21.3%), while current result was higher than that reported byDisha et al., …”
supporting
confidence: 88%
“…While Saudi Arabia provides free public orthodontic treatment services, individuals with severe treatment needs face delayed access to relevant facilities compared with those with minor orthodontic treatment procedures. 23 Therefore, it is necessary to increase awareness of the importance of FPM and the consequences caused by the early loss of FPM teeth.…”
Section: Discussionmentioning
confidence: 99%